Contribution of Orexin to the Neurogenic Hypertension in BPH/2J Mice. Issue 5 (May 2016) - Jackson, Kristy L.; Dampney, Bruno W.; Moretti, John-Luis; Stevenson, Emily R.; Davern, Pamela J.; Carrive, Pascal; Head, Geoffrey A.
Abstract : BPH/2J mice are a genetic model of hypertension associated with an overactive sympathetic nervous system. Orexin is a neuropeptide which influences sympathetic activity and blood pressure. Orexin precursor mRNA expression is greater in hypothalamic tissue of BPH/2J compared with normotensive BPN/3J mice. To determine whether enhanced orexinergic signaling contributes to the hypertension, BPH/2J and BPN/3J mice were preimplanted with radiotelemetry probes to compare blood pressure 1 hour before and 5 hours after administration of almorexant, an orexin receptor antagonist. Mid frequency mean arterial pressure power and the depressor response to ganglion blockade were also used as indicators of sympathetic nervous system activity. Administration of almorexant at 100 (IP) and 300 mg/kg (oral) in BPH/2J mice during the dark-active period (2 hours after lights off) markedly reduced blood pressure (−16.1±1.6 and −11.0±1.1 mm Hg, respectively; P <0.001 compared with vehicle). However, when almorexant (100 mg/kg, IP) was administered during the light-inactive period (5 hours before lights off) no reduction from baseline was observed ( P =0.64). The same dose of almorexant in BPN/3J mice had no effect on blood pressure during the dark ( P =0.79) or light periods ( P =0.24). Almorexant attenuated the depressor response to ganglion blockade ( P =0.018) and reduced the mid frequency mean arterial pressure power in BPH/2J mice ( P <0.001), but not BPN/3J mice ( P =0.70). Immunohistochemical labeling revealed that BPH/2J mice have 29% more orexin neurons than BPN/3J mice which are preferentially located in the lateral hypothalamus. The results suggest that enhanced orexinergic signaling contributes to sympathetic overactivity and hypertension during the dark period in BPH/2J mice. Abstract : Supplemental Digital Content is available in the text.